ENVIRONMENTAL QUALITY FACTORS AND DENSITY OF ANOPHELES LARVAE AGAINST MALARIA ENDEMICITY IN INDONESIA. A SYSTEMATIC REVIEW - Mursid Raharjo; Martini Martini2; Retno Hestiningsih; -, Fitni Hidayati (Journal of Community Medicine and Public Health Research, 2022)
Malaria is still a serious problem of health in tropical and subtropical climates. The potential for malaria has become a global concern with increasing morbidity and mortality rates. Millions of people die every year, and 80% of them occur in children. Indonesia is included in the highest level of malaria excess in the world, after India in 2020. In 2021, malaria in Indonesia reached 94,610 cases. Of 34 provinces in Indonesia, 31 provinces still have confirmed cases of malaria. Malaria is caused by the female Anopheles mosquito containing plasmodium. Anopheles mosquitoes have preferred behavior in the process of breeding, resting, and biting, according to the environmental conditions of their habitat. Therefore, this literature discusses several environmental quality factors (temperature, humidity, rainfall, wall conditions, gauze wire on ventilation, ceiling of the house, presence of bushes, and presence of standing water) and the density of Anopheles larvae on the incidence of malaria. This research was conducted in the form of a literature review using the Sinta database as reference material. Based on a study of 16 scientific journals, there were 11 scientific journals regarding significant risk factors for the incidence of malaria and 5 journals regarding Anopheles larvae density.Malaria is still a serious problem of health in tropical and subtropical climates. The potential for malaria has become a global concern with increasing morbidity and mortality rates. Millions of people die every year, and 80% of them occur in children. Indonesia is included in the highest level of malaria excess in the world, after India in 2020. In 2021, malaria in Indonesia reached 94,610 cases. Of 34 provinces in Indonesia, 31 provinces still have confirmed cases of malaria. Malaria is caused by the female Anopheles mosquito containing plasmodium. Anopheles mosquitoes have preferred behavior in the process of breeding, resting, and biting, according to the environmental conditions of their habitat. Therefore, this literature discusses several environmental quality factors (temperature, humidity, rainfall, wall conditions, gauze wire on ventilation, ceiling of the house, presence of bushes, and presence of standing water) and the density of Anopheles larvae on the incidence of malaria. This research was conducted in the form of a literature review using the Sinta database as reference material. Based on a study of 16 scientific journals, there were 11 scientific journals regarding significant risk factors for the incidence of malaria and 5 journals regarding Anopheles larvae density.